The Role of Effectiveness of Emotional Intelligence and Digital Literacy on Creative Thinking Ability and Its Implications for Teacher Performance in Private Vocational High Schools in Pandeglang Regency - Sri Rahayu Sangra Dempo; Furtasan Ali Yusuf; Uli Wildan Nuryanto (LPPPIPublishing, 2023)
The purpose of this research is to analyze the role of effectiveness of emotional intelligence and digital literacy on creative thinking ability and its implications for teacher performance in Private Vocational High Schools in Pandeglang Regency. This type of research uses quantitative research. The research population here is the teachers of Private Vocational High Schools in Pandeglang Regency, totaling 913 people. Based on the calculation of the minimum number of samples to be taken is 248 people. This study uses structural equation modeling (SEM)-partial least square (PLS) analysis techniques. The results of the study show that emotional intelligence has no significant effect on creative thinking ability in Private Vocational High Schools in Pandeglang Regency. Emotional intelligence has a significant effect on teacher performance in Private Vocational High Schools in Pandeglang Regency. Digital literacy has a significant effect on creative thinking ability in Private Vocational High Schools in Pandeglang Regency. Digital literacy has a significant effect on teacher performance in Private Vocational High Schools in Pandeglang Regency. Creative thinking ability has a significant effect on teacher performance in Private Vocational High Schools in Pandeglang Regency. Creative thinking ability is not able to significantly moderate effect of emotional intelligence on teacher performance in Private Vocational High Schools in Pandeglang Regency. Creative thinking ability is able to significantly moderate effect of digital literacy on teacher performance in Private Vocational High Schools in Pandeglang Regency.